Construction of Robust Iridium(III) Complex-Based Photosensitizer for Boosting Hydrogen Evolution - Wang, Yue; Huang, Yifan; Chen, Shuang; Gao, Jian; Zhang, Yifan; Duan, Ying-chen; Deng, Pengyang (Inorganic chemistry, 2023)
Developing a photosensitizer with high efficiency and long-term stability for photocatalytic hydrogen evolution is highly desirable yet remains a challenge. Herein, a novel Ir(III) complex-based photosensitizer (Ir3) bearing coumarin and triphenylamine groups is designed. Ir3 exhibits record activity and durability among reported transition metal complexes for photocatalytic hydrogen evolution, with a TON of 198,363 and a duration of 214 h. The excellent photocatalytic performance of Ir3 can be attributed to the synergistic effect of coumarin and triphenylamine, which improves the visible light absorption, charge separation, and electron transfer capacity of photosensitizers. This is an efficient and long-lived Ir(III) photosensitizer constructed on the basis of a synergistic approach, which could provide a new insight for the development of high-performance Ir(III) photosensitizers at the molecular level.